Case report: State-of-the-art risk-modifying treatment of sudden cardiac death in an asymptomatic patient with a mutation in the SCN5A gene and a review of the literature - Brlek, Petar; Pavelić, Eduard Stjepan; Mešić, Jana; Vrdoljak, Kristijan; Skelin, Andrea; Manola, Šime; Pavlović, Nikola; Ćatić, Jasmina; Matijević, Gordana; Brugada, Josep; Primorac, Dragan (Frontiers in Cardiovascular Medicine, 2023)
Brugada syndrome is a rare hereditary disorder characterized by distinct ECG findings, complex genetics, and a high risk of sudden cardiac death. Recognition of the syndrome is crucial as it represents a paradigm of sudden death tragedy in individuals at the peak of their lives. Notably, Brugada syndrome accounts for more than 20% of sudden cardiac deaths in individuals with structurally normal hearts. Although this syndrome follows an autosomal dominant inheritance pattern, it is more prevalent and severe in males. Diagnosis is primarily based on the characteristic ECG pattern observed in the right precordial leads. Mutations in the SCN5A gene, resulting in loss of function, are the most common genetic cause. We presented a 36-year-old proband with a family history of sudden cardiac death. Although the patient was asymptomatic for Brugada syndrome, his father had experienced sudden death at the age of 36. The proband was admitted to St. Catherine's Specialty Hospital where genomic DNA was isolated and subjected to next-generation sequencing (NGS) using a "Sudden cardiac death" panel. The analysis identified a pathogenic variant in the SCN5A gene (c.4222G>A(p.Gly1408Arg)), which is associated with autosomal dominant Brugada syndrome. Based on the positive genetic test result, the patient was referred for further examination. ECG with modified precordial lead positioning confirmed the presence of the Brugada phenotype, displaying the type-2 and type-1 ECG patterns. Therefore, we made the diagnosis and decided to implant an implantable cardioverter-defibrillator (ICD) based on the results of broad genetic NGS testing, diagnostic criteria (ECG), and considering the high burden of sudden cardiac death in the patient's family, as well as his concerns that limited his everyday activities. This case shows that genetics and personalized medicine hold immense potential in the primary prevention, diagnosis, and treatment of Brugada syndrome and sudden cardiac death.